2003
DOI: 10.1103/physrevb.67.115314
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of the adsorption and reaction of cyclopentene on Ge(001)

Abstract: The adsorption and reaction of cyclopentene on the Ge͑001͒ surface is investigated by first-principles density-functional calculations within the generalized gradient approximation. Surprisingly, a recent cluster calculation for adsorbed cyclopentene on Ge͑001͒ obtained an adsorption energy of 2.10 eV, which is larger than the same cluster result ͑1.65 eV͒ on Si͑001͒. However, our calculated adsorption energy for 0.5͑1͒monolayer cyclopentene on Ge͑001͒ is 0.79͑0.51͒ eV, comparable with an observed activation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Recent theoretical studies [10][11][12][13][14]16,34 have also suggested the importance of hydrogen bonding in H 2 O, NH 3 , and CH 3 NH 2 adsorption on Si͑001͒. A typical hydrogen bond ͑between a positively charged H atom and a small electronegative atom such as O and N͒ is about 0.2 eV in the gas phase.…”
Section: Hydrogen Bondingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent theoretical studies [10][11][12][13][14]16,34 have also suggested the importance of hydrogen bonding in H 2 O, NH 3 , and CH 3 NH 2 adsorption on Si͑001͒. A typical hydrogen bond ͑between a positively charged H atom and a small electronegative atom such as O and N͒ is about 0.2 eV in the gas phase.…”
Section: Hydrogen Bondingmentioning
confidence: 99%
“…Similarly, using DFT-slab calculations Cho and Kleinman 16 have predicted the alignment of dissociated CH 3 NH moieties by the N…H hydrogen-bonding interaction. However, recent DFT-slab calculation results reported by Wang and Hwang 10 have suggested that both molecular and dissociative CH 3 NH 2 adsorption structures at the saturation coverage prefer the zigzag arrangement due to adsorbate-adsorbate repulsion.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption energy for this situation is −63.4 kcal mol −1 . A previous study, adsorbing not ACP but methylamine 18 at a concentration of 0.5 ML with DFT-GGA and a periodic slab, found an amine adsorption energy of −32.5 kcal mol −1 for the undissociated state, −47.0 kcal mol −1 for the H-dissociated state, and −60.2 kcal mol −1 for the C-dissociated state. We can see that the behavior of ACP when adsorbing through the amine group is basically similar to the one found for other amines.…”
Section: Resultsmentioning
confidence: 85%
“…This makes us predict that although the cyclopentenedissociated N-adsorbed ACP may have the highest adsorption energy, it must be very unlikely as it involves the breaking of a nitrogen-carbon bond which correlates to a very high energy transition state, while the H-dissociated form only involves a proton transfer between the amine and a silicon atom. 16,18 For other amines, the energy of the transition state involved in a C-dissociation was always above the energy of the free reagents by a prohibitive amount, hence, observing the conservative behavior of ACP, it is fair to assume that C-dissociation is nearly impossible. The three N-adsorbed structures are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation